2022
DOI: 10.21037/atm-21-6916
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA NEAT1 inhibits the proliferation of human cutaneous squamous cell carcinoma in vivo and in vitro

Abstract: Background: The incidence of cutaneous squamous cell carcinoma (CSCC), a malignant tumor that threatens human life, is increasing every year, and yet its pathogenesis is still unclear. This study found that long noncoding RNA (lncRNA) nuclear-enriched abundant transcript 1 (NEAT1) was abnormally expressed in CSCC. However, the biochemical mechanisms of lncRNA NEAT1 in carcinogenesis and the development of cancer remain unclear.Methods: Fluorescence quantitative polymerase chain reaction (qPCR) was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, PRECSIT has been shown to increase the invasion of cSCC cells by regulating the expression of MMPs via STAT3 signaling [ 18 ]. Additionally, recent studies have implicated lncRNAs HOTAIR [ 38 ], NEAT1 [ 39 ], and MALAT1 [ 40 ] in the progression of cSCC. Furthermore, LINC00319 has been noted to regulate the invasion of cSCC cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PRECSIT has been shown to increase the invasion of cSCC cells by regulating the expression of MMPs via STAT3 signaling [ 18 ]. Additionally, recent studies have implicated lncRNAs HOTAIR [ 38 ], NEAT1 [ 39 ], and MALAT1 [ 40 ] in the progression of cSCC. Furthermore, LINC00319 has been noted to regulate the invasion of cSCC cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…in CSCC Tissues. Our previous study demonstrated that lncRNA NEAT1 was overexpressed in CSCC tissues [11].…”
Section: Correlation Of Mir-342-3p and Lncrna Neat1 Expressionmentioning
confidence: 96%
“…As colorectal cancer development and metastasis are facilitated by the stimulation of the Wnt signaling pathway activated through lncRNA NEAT1, the lncRNA NEAT1/DDX5/Wnt/-catenin axis might be an effective therapeutic target [10]. Knockdown of lncRNA NEAT1 was demonstrated to significantly decrease the proliferation and invasion of CSCC [11]. However, the mechanism by which lncRNA NEAT1 controls cell proliferation and invasion is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…LncRs are more than 200 bases long and are species/tissue specific. LncRs can interact with DNA, RNA, and proteins to regulate a wide range of biological processes [ 149 , 150 ]. Recent microarray analyses and next-generation sequencing assays have found that lncRs can modulate gene expression at multiple levels, including regulation at the epigenetic, transcriptional, and post-transcriptional levels.…”
Section: Involvements Of Lncrs In Rstapsmentioning
confidence: 99%